Organic wastes as soil amendments - Effects assessment towards soil invertebrates - Renaud, Mathieu (2019)
Using organic wastes, as soil amendments, is an important alternative to landfilling with benefits to soil structure, water retention, soil nutrient and organic matter concentrations. However, this practice should be monitored for its environmental risk due to the frequent presence, of noxious substances to soil organisms. To evaluate the potential of eight organic wastes with different origins, as soil amendments, reproduction tests with four soil invertebrate species (Folsomia candida, Enchytraeus crypticus, Hypoaspis aculeifer, Eisenia feticta) were performed using gradients of soil waste Mixtures. Results obtained demonstrated that contaminant concentrations required by current legislation might not be a protective measure for the soil ecosystem, as they do not properly translate the potential toxicity of wastes to soil invertebrates. Some wastes with contaminant loadings below thresholds showed higher toxicity than wastes with contaminants concentrations above legal limits. Also, test organism reproduction was differently sensitive to the selected wastes, which highlights the need to account for different organism sensitivities and routes of exposure when evaluating the toxicity of such complex mixtures. Finally this study shows that when combining chemical and ecotoxicological data, it is possible to postulate on potential sources of toxicity, contributing to better waste management practices and safer soil organic amendment products. (C) 2017 Elsevier B.V. All rights reserved.